A nonlocal problem multipoint by time for one class of evolutionary singular equations - Gorodetskii, V.V.; Martynyuk, O.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The solvability of a nonlocal problem multipoint by time for evolutionary equations with pseudo-Bessel infinite-order operators with an initial condition that is an element of the space of generalized functions of the dis tribution type is established in the case where the nonlocal multipoint condition contains pseudo-Bessel ope rators.